Prevalence and Pattern of Oral Diseases in Diabetic Patient (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: The present case-control study was conducted to assess the prevalence and pattern of oral diseases among patients with diabetes.Methods: The study was conducted at the Department of Dentistry, Shaheed Khalek-Ibrahim General Hospital (An Institution of Diabetic Association of Bangladesh), Dhaka, from April to September 2010 using a case-control design. A total of 100 subjects— 47 diabetics and 53 non-diabetics— who met the eligibility criteria were consecutively selected from outpatient attendees. Diabetic status was confirmed, and controls were free of diabetes. Data on socio-demographics, oral health practices, and clinical oral conditions were collected and analyzed.Results: Diabetic patients were significantly older than controls (p